КЕРУВАННЯ ДИНАМІКОЮ ІМПУЛЬСНОГО ПЕРЕТВОРЮВАЧА З М’ЯКИМ ПЕРЕМИКАННЯМ, ЩО ПРАЦЮЄ НА ДУГОВЕ НАВАНТАЖЕННЯ - Верещаго, Є.М.; Костюченко, В.І.; Стогнієнко, Є.В.; Грєшнов, А.Ю. (Інститут електродинаміки НАН України, Київ, 2024)
Issues of design and research of energy-efficient and reliable semiconductor DC voltage converters for wide application in power supply devices of arc plasmatrons used in plasma metal cutting installations are considered. An estimated structural dynamic model of a soft-switching DC converter with a closed-loop control system combining the power part and the control system, intended for use as part of the latter as a digital module, was built. A technique is proposed and methods of controlling the converter are found, which provide the specified duration of transient processes, the permissible value of load current pulsations in a quasi-steady mode and the astatism of the output current, which confirms the correctness of the proposed technique. A prototype of a pulse stabilizer with digital control was made. The results of experimental studies of the sample confirm the effectiveness of the developed control device, namely the achievement of the specified duration of transient processes caused by a step change in the load current, close to 10-12 periods of conversion and astatism of the output current. It is shown that the application of a pulse stabilizer, in which a digital control loop is used, has significant advantages compared to analog options and has the advantages of a strategic plan. The use of combined control allows you to significantly reduce the requirements for the overall gain of the main control channel, which greatly facilitates the choice of sequential digital correction. Research results may be of interest to specialists in the field of power electronics, power supply systems of autonomous objects and control systems. References 14, figures 11.